2022
DOI: 10.1186/s12959-022-00442-7
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors and potential predictors of pulmonary embolism in cancer patients undergoing thoracic and abdominopelvic surgery: a case control study

Abstract: Background Postoperative pulmonary embolism (PE) is a severe complication leading to death and poor prognosis. The present study investigated the risk factors and potential predictors of PE in cancer patients undergoing thoracic and abdominopelvic surgery. Methods A retrospective study was conducted on the patients with cancer who underwent thoracic and abdominopelvic surgery in Sichuan Cancer Hospital from December 2016 to January 2022. A total of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 39 publications
1
0
0
Order By: Relevance
“…In a study by Li et al [32], IOH was found associated with increased postoperative complications including thromboembolic events. In our previous study, we found IOH was an independent risk factor of PE in cancer patients undergoing thoracic and abdominopelvic surgery [33]. IOH time was also identi ed as a risk factor for early PE in patients with cancer according to Lasso regression in this study.…”
Section: Discussionsupporting
confidence: 64%
“…In a study by Li et al [32], IOH was found associated with increased postoperative complications including thromboembolic events. In our previous study, we found IOH was an independent risk factor of PE in cancer patients undergoing thoracic and abdominopelvic surgery [33]. IOH time was also identi ed as a risk factor for early PE in patients with cancer according to Lasso regression in this study.…”
Section: Discussionsupporting
confidence: 64%